Answer:
The correct answer is: Option 1: x≤-3
Explanation:
Given inequality is:
![-6x-4\geq -2(x-4)](https://img.qammunity.org/2022/formulas/mathematics/college/l87kb3vw46da50zi49uca7f0khmljqa22d.png)
First of all, we will distribute -2 into the bracket
![-6x-4\geq -2x+8](https://img.qammunity.org/2022/formulas/mathematics/college/9v719p6ey3fu0bo0nvq7tk2t9n99kpn1pp.png)
Then we will add 4 on both sides
![-6x-4+4\geq -2x+8+4\\-6x \geq -2x+12](https://img.qammunity.org/2022/formulas/mathematics/college/yihnjllsto1dnf02j55upwe5yfjxn3gn7m.png)
Adding 2x on both sides
![-6x+2x\geq -2x+12+2x\\-4x\geq 12](https://img.qammunity.org/2022/formulas/mathematics/college/5wmd95ra55hlix7cj3w9qt3vom6vqotins.png)
Dividing both sides by 4
![(-4x)/(4) \geq (12)/(4)\\-x \geq 3](https://img.qammunity.org/2022/formulas/mathematics/college/5hmhxu1ke6htrfbcb6kc2xuc4a21lnjm0h.png)
As there should be only x on the left side of the inequality we will multiply the inequality with -1.
Multiplying the inequality with -1 reverses the sign of inequality
So,
![x \leq -3](https://img.qammunity.org/2022/formulas/mathematics/college/7860n9nvkf56pr3118ikj6fj4bwmauiy0e.png)
Hence,
The correct answer is: Option 1: x≤-3